Pharmacokinetics and Metabolism of the Novel Muscarinic Receptor Agonist SNI-2011 in Rats and Dogs - Washio, Takuo; Kohsaka, Kazuhiro; Arisawa, Hirohiko; Masunaga, Hiroaki (Arzneimittelforschung, 2003)
In this study, the pharmacokinetics of SNI-2011 ((±)-cis-2-methylspiro[1,3-oxathiolane-5,3’-quinuclidine]monohydrochloride hemihydrate, cevimeline, CAS 153504-70-2), a novel muscarinic acetylcholine receptor agonist developed for the treatment of Sjögren’s syndrome, in rats and dogs were determined following intravenous or oral administration using liquid chromatography/mass spectrometry (LC/MS). The in vitro metabolism of SNI-2011 was also evaluated with rat and dog liver microsomes. After oral administration, plasma concentrations of SNI-2011 reached to Cmax within 1 h in both species, suggesting that SNI-2011 was quickly absorbed, and then decreased with a t1/2 of 0.4–1.1 h. The bioavailability was approximately 50 % and 30 % in rats and dogs, respectively.Major metabolites in plasma were both S- and N-oxidized metabolites in rats and only N-oxidized metabolite in dogs, indicating that a large species difference was observed in the metabolism of SNI 2011. Sex difference was also observed in the pharmacokinetics of SNI-2011 in rats, but not in dogs. In the in vitro study, chemical inhibition and pH-dependent studies revealed that the sulfoxidation and N-oxidation of SNI-2011 were mediated by cytochrome P450 (CYP) and flavin-containing monooxygenase (FMO), respectively, in both species. In addition, CYP2D and CYP3A were mainly responsible for the sulfoxidation in rat liver microsomes.
Keywords: CAS 153504-70-2; Cevimeline; SNI-2011, dog, metabolism, pharmacokinetics, rat